COVID-19 in a tertiary paediatric centre in Portugal: a single-centre retrospective study - Ana Margarida Garcia; Catarina Gouveia; Maria João Brito; Tiago Milheiro Silva; Flora Candeias (BMJ Publishing Group, 2022)
Objective To describe the demographic, clinical, laboratory and imaging features of the first 300 SARS-CoV-2-infected children presenting to a tertiary paediatric centre in Portugal.Design Single-centre, retrospective, descriptive study of paediatric patients who had a confirmed SARS-CoV-2 infection from 7 March to 20 September 2020.Setting Tertiary paediatric referral centre (Hospital Dona Estefânia, Lisbon, Portugal).Patients 18 years or younger.Main outcome measures Incidence, mortality, age of infection, clinical characteristics, treatment prescribed and outcome.Results Three hundred patients with confirmed COVID-19 presented to the centre. One hundred and seventeen (39%) patients were admitted to the hospital: 69 with COVID-19 and 48 for other reasons. The most common symptoms in children admitted with COVID-19 were fever (49) and cough (38). Six patients required intensive care. Two children died and seven reported short-term sequelae.Conclusions COVID-19 is usually a mild disease in children, but a small proportion of patients develop severe and critical disease. Fatal outcomes were rare and only occurred in children with severe previous medical conditions.